MEMAHAMI PERAN MASYARAKAT DAN PEMERINTAH DALAM KEMAJUAN MUTU PENDIDIKAN DI INDONESIA - Temon Astawa, I Nyoman (LPM IHDN Denpasar, 2017)
The development of the quality of education in Indonesia should be done together not only for the government and educators but to the community, because the community has an important role to achieve a goal of educationquality. In fact in the field of our education system fully devolved public education students or learners to teachers. This can be caused by a lack of public understanding of the importance of the role of the community in education.